GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 7332041 species occurrences available in GBIF matching the query: BasisOfRecord: Living Specimen or Literature Occurrence or Fossil. The dataset includes 7332041 records from 316 constituent datasets: 155 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 653 records from Colección nacional de palmas de Colombia - JBQ. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 12 records from Colección de Exhibición de Fósiles del Museo de Ciencias de la Universidad El Bosque. 747 records from LACM Entomology Collection. 1 records from New records in vascular plants alien to Kyrgyzstan. 4 records from Fossil (SMNH-FO). 2007 records from Palaeobiology collection, FAU Erlangen. 568 records from Coleccion Paleoinvertebrados CCT Mendoza - CONICET. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 5194 records from SMNS Palaeontological collection - Amber and fossil insects. 4766 records from Paläontologie Marburg. 25 records from Hyolithen - SMF. 9349 records from Harriet Irving Botanical Gardens (HIBG). 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 99463 records from NPL collections. 99 records from French national collection of Solanum tuberosum. 73974 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 51969 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 660 records from VMNH Invertebrate Paleontology. 2082 records from Vietnam Type Culture Collection. 52 records from BioFokus. 355 records from Culture Collection of Cryophilic Algae. 32 records from Archaea Collection in BCRC. 377096 records from University of Florida Vertebrate Paleontology. 56 records from BioAcoustica: Wildlife Sounds Database. 514 records from SDSM Vertebrate Paleontology Collection. 22137 records from Global compendium of Aedes albopictus occurrence. 50 records from CIM Specimens. 6 records from MfN - Micropaleontology. 777 records from INRA-Versailles Arabidopsis natural variants. 2412 records from Ohio University Invertebrate Paleontology Collection. 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 132 records from Fiocruz/CCAMP - Coleção de Campylobacter. 860 records from Digital Florula - Las Cruces Biological Station. 1 records from SDSM Botany and Paleobotany Collections. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 5 records from Lund Museum of Zoology (MZLU). 1641 records from NCSM PaleoBotany Collection. 1614 records from Culture Collection of Algae. 210019 records from Invert Paleo Specimens. 201423 records from Museum of Comparative Zoology, Harvard University. 192907 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 98 records from Colección Nacional de Heliconias. 807 records from Reunion_Coffea. 18900 records from UCBG TAPIR Provider. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 400183 records from University of California Museum of Paleontology. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 79406 records from KUBI Vertebrate Paleontology Collection. 1266 records from Actinomycetes Collection in BCRC. 643600 records from NMNH occurrence DwC-A. 959 records from SMNS Palaeontological collection - Fossil mammals. 29264 records from NCSM Vertebrate Paleontology Collection. 5450 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 1734 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 7950 records from European riparian ground beetles. 97343 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 12910 records from SMNS Palaeontological collection - Invertebrates (Jurassic and Cretaceous). 13938 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 2813 records from UTEX Culture Collection of Algae at The University of Texas Living Algae Holdings. 36845 records from MfN - Fossil invertebrates Ia. 282 records from MfN - Fossil invertebrates IIa. 7346 records from MfN - Fossil vertebrates III. 44 records from MfN - Fossil invertebrates Ib. 1649 records from MfN - Trace fossils. 14660 records from MfN - Fossil invertebrates IIb. 23319 records from MfN - Fossil invertebrates III. 142 records from MfN - Fossil vertebrates I. 77414 records from MfN - Fossil vertebrates IV. 16479 records from MfN - Fossil plants (Cenophytic). 8532 records from MfN - Fossil plants (Mesophytic). 13945 records from MfN - Fossil plants (Paleophytic). 4310 records from MfN - Fossil vertebrates V. 2 records from MfN - Glacial erratics. 4 records from MfN - Fossil vertebrates II. 15 records from MfN - Fossil plants II. 536 records from AlgaTerra. 11343 records from Natural History Museum Rotterdam (NL) - Chordata collection. 209 records from Pinos del Noreste de México (UANL). 545 records from Colección de Aves y Mamíferos del Valle de Cuatrociénegas, Coah., México (UANL). 3012 records from GSPB Prokarya Catalogue. 24583 records from Jardin botanique de Montréal (JBM). 101319 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 603 records from Fossil (NSMK-FO). 3362 records from Coimbra Collection of Algae. 1418 records from Fossil (GNHM-FO). 1603 records from Fossil (MNHM-FO). 1288 records from Tiroler Landesmuseum Ferdinandeum. 1 records from The Lichen Collection at the Botanische Staatssammlung München. 63 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 135 records from Natural History Museum Rotterdam (NL) - Invertebrata miscellaneous Collection. 12037 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 280 records from EDIT - ATBI in Spreewald (Germany). 3264 records from SMNS Palaeontological collection - Invertebrates (Cenozoic). 8299 records from Mammalia fossil Kleinsäuger - SMF. 25942 records from Institut Mediterrani d'Estudis Avançats: IMEDEA-PALEOVERT. 4 records from Sistemática del género Polianthes L (Agavaceae). 2346 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 1278 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 4 records from Revisión taxonómica del género Furcraea (Agavaceae) en México y Guatemala. 1544 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 203 records from Catálogo de autoridad taxonómica del género Quercus, Fagaceae en México. 372 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 503 records from Inventario fitopatológico de las especies vegetales dominantes en la región de Zapotitlán de las Salinas, Pue.. 1057 records from Helmintos de peces dulceacuícolas de México. 19 records from Inventario florístico de la Frailescana (zona focal), Chiapas, México. 11 records from Anfibios y reptiles del estado de Nuevo León. 311 records from Flora de macroalgas del litoral oaxaqueño. 12 records from Ficha de Sonora aemula. 932 records from Distribución geográfica de las aves y los mamíferos del estado de Querétaro. 1278 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 3670 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 569 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 985 records from Biodiversidad de moluscos opistobranquios (Mollusca: Opisthobranchiata), del Pacífico mexicano: Isla Cedros-Vizcaíno e islas del Golfo de California parte Sur. 2953 records from Avifauna de la laguna Madre de Tamaulipas. 181 records from Diversidad y riqueza vegetal de los substratos rocosos del centro del estado de Veracruz. 2074 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Aves. 223478 records from NatureServe Network Species Occurrence Data. 784 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 1252 records from Distribución, abundancia y riqueza específica de la avifauna terrestre en la Isla Espíritu Santo, Baja California Sur, México. 853 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Mamíferos. 173 records from Herpetofauna de la reserva de la biósfera Valle de Tehuacán-Cuicatlán (etapa final). 311 records from Elasmobranquios del sistema laguna Chantuto-Panzacola y Carretas-Pereyra de la Reserva de la Biósfera La Encrucijada, Chiapas. 1052 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus) en México. 12 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán (continuación). 11 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán. 446 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 37 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 12 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla. 399 records from Distribución y aspectos taxonómicos de los corales pétreos (Anthozoa: Scleractinia) del Pacífico mexicano. 1954 records from Deforestación y fragmentación del hábitat: consecuencias ecológicas sobre la fauna de mamíferos de la selva tropical estacional. 3 records from Inventario ficoflorístico de las comunidades arrecifales del Parque Nacional Bahías de Huatulco, Oaxaca. 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Bosques. 4 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 89 records from Flora de las Barrancas del Cobre. 225 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 36 records from Inventario nacional de especies vegetales y animales de uso artesanal. 680 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 22 records from Potencial económico de la flora útil de los cafetales de la Sierra Norte de Puebla. 50 records from Ictiofauna insular del medio y bajo Golfo de California. 18377 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 68 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 2009 records from Vertebrados silvestres en zonas indígenas de la reserva de la biósfera Mariposa Monarca: anfibios y reptiles. 2126 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 6 records from Evaluación de la ictiofauna en las áreas focales del corredor biológico costero-Yucatán. 108 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Peces. 3029 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 3 records from Diversidad bentónica del ambiente intermareal e infralitoral somero de Progreso, Yucatán. 1 records from Computarización de las Colecciones de Anfibios y Reptiles del Centro de Investigaciones Biológicas de la Universidad Autónoma del Estado de Hidalgo. 2441 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 535 records from Herpetofauna del corredor biológico Chichinautzin y la Sierra de Huautla en el estado de Morelos. 2042 records from Elasmobranquios del Golfo de Tehuantepec, litoral chiapaneco. 4512 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 4 records from Inventario de los ropaloceros (Lepidoptera) de la Sierra Gorda, estado de Querétaro, México. 1009 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Mariposas. 2651 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 96 records from Inventario de los murciélagos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, Baja California, México. 160 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 473 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 1617 records from Helmintos parásitos de peces del sureste de México. 4626 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 453 records from Distribución e inventario de algunas especies bentónicas (hexacorales, octocorales, esponjas, y especies misceláneas) en arrecifes del Caribe mexicano. 42 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 1092 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 440 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 19 records from Ictiofauna de la Bahía de Banderas Nayarit, Jalisco y zonas adyacentes, México. 4985 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 65 records from Avifauna de la reserva de la biosfera El Cielo, Tamaulipas, México. 515 records from Inventario de la biota terrestre (florístico) del parque nacional Isla Isabel. 272 records from Límites de especies dentro del género Gerrhonotus (Sauria: Anguidae). 130 records from Helmintos parásitos de peces de lagunas costeras de Jalisco, México. 1216 records from Inventario de la biota marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 114 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 77 records from Programa de erradicación de los roedores introducidos en la Isla Rasa, Baja California: un plan de restructuración ecológica. 692 records from Collection Trilobita SMF. 4 records from Shellfish specimens in the NISHINOMIYA SHELL MUSEUM, Japan.. 63856 records from IG TUT paleontology. 31531 records from Tartu University, palaeontology collections. 880 records from Collection Paleobotanique de l'Universite Paris 6. 603 records from Collection of Industrial Microorganisms. 2374 records from DSMZ Collection of Filamentous Fungi and Yeasts. 899 records from Collection Insecta fossil - SMF. 8231 records from Collection Bernstein - SMF. 45 records from Collection Arachnologie fossil - SMF. 856 records from Collection Hunsrückschiefer - SMF. 4433 records from Röntgenarchiv Wilhelm Stürmer - SMF. 6 records from Corvids Literature Database. 203 records from The Himalayan Uplands Plant database (HUP Version 1). 9266 records from Naturhistorisches Museum Mainz, Paleontological Collection. 2833 records from Botanical Garden Collection. 49459 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 24958 records from CABI Bioscience Genetic Resource Collection. 277 records from Natural Geography In Shore Areas (NaGISA) Dataset. 7349 records from Botanic Garden of the Finnish Museum of Natural History. 10741 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 764816 records from Paleobiology Database. 153 records from California Beetle Project. 24798 records from University of Copenhagen Arboretum. 4664 records from Database Schema for UC Davis [TGRC]. 6037 records from Database Schema for UC Davis [Phaff]. 5593 records from UCD BOTANICAL CONSERVATORY. 153 records from Rosaceae and Fabaceae of Kevo region, Northern Finland. 355377 records from Invertebrate Paleontology Division, Yale Peabody Museum. 2440 records from Colección Nacional de Icnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 6 records from Desmidiaceae Rostock. 22838 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 322 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 704 records from DSMZ Collection on Plant Cell Cultures. 37614 records from Nordic Genetic Resources. 2255 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 19417 records from DSMZ Prokarya Collection Catalogue. 690 records from DSMZ Collection of Plant Viruses. 11622 records from French Grapevine Genetic Resources Center. 3 records from Acari fossil - SMNG. 1535 records from Mushroom Collection in BCRC. 944 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (siembra). 508 records from Guyane_Cacaoyer. 373 records from Cactáceas Columnares de México (IE-MORELIA, UNAM). 1 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 76872 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 251 records from Micoteca da Universidade do Minho. 3343 records from SMNS Palaeontological collection - Fossil aquatic vertebrates. 150 records from Vegetatively propagated Allium collection. 7351 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 763 records from Global subterranean fishes. 59948 records from Polish gene bank – passport data of plants accessions which are important in human life. 779 records from CSIRO, Australian National Algae Culture Collection, Global, 1949-2008. 172 records from EEIKO Base de datos sobre plantas invasoras. 1 records from Therevid PEET Project. 10577 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 120 records from EDIT - ATBI in Gemer area (Slovakia). 19953 records from ELM paleontology. 9952 records from Biological and palaeontological collection and observation data MNHNL. 2 records from Botany Division, Yale Peabody Museum. 91237 records from Paleobotany Division, Yale Peabody Museum. 73596 records from Vertebrate Paleontology Division, Yale Peabody Museum. 212930 records from KU Museum of Invertebrate Paleontology. 2294 records from Collection Echinodermata fossil SMF. 63 records from Collection Mikropaläobotanik SMB. 1674 records from Collection Paläobotanik SMB. 3106 records from Collection Cnidaria fossil SMF. 2385 records from Collection Messelpaläobotanik SMB. 3056 records from Collection Brachiopoda fossil SMF. 904 records from Collection Agnatha fossil SMF. 13 records from Collection Reptilia fossil SMF. 3 records from Collection Aves fossil SMF. 68 records from Collection Tentakulita fossil SMF. 923 records from Collection Graptolithina fossil SMF. 1 records from Collection Quaternary Small Mammals IQW. 1 records from Collection Mammalia fossil SMF. 21900 records from Jena Microbial Resource Collection (JMRC) at Leibniz Institute for Natural Product Research and Infection Biology e.V. Hans-Knöll-Institute (HKI) and Friedrich Schiller University Jena. 252944 records from University of Florida Invertebrate Paleontology. 35667 records from UAM Earth Sciences Collection (Arctos). 429 records from NODAI Culture Collection Center, Tokyo University of Agriculture, Japan. 176 records from Jardín Botánico Uniamazonia JBUA. 1 records from First record of Eggplant Mealybug, Coccidohystrix insolita (Hemiptera: Pseudococcidae), on Guam: Potentially a major pest. 1781 records from Soft Wheat French National Collection. 88826 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 15975 records from condoncollection. 3027 records from Fungi Collection in BCRC. 1 records from Siphonaptera fossil - SMNG. 16809 records from Genebank, National Institute of Agrobiological Sciences. 96 records from Guadeloupe_manguier. 1070 records from SMNS Palaeontological collection - Amphibians, reptiles (Palaeozoic, Mesozoic). 1853 records from Yeast Collection in BCRC. 262623 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 186 records from The Fish Database of Taiwan. 8391 records from SBT-Living. 44502 records from Condon Fossil Collection. 11661 records from NCSM Invertebrate Paleontology Collection. 72590 records from CU Invertebrate Paleontology. 721 records from Microbial Culture Collection, National Institute for Environmental Studies. 9614 records from University of British Columbia Botanical Garden Collections (UBCBG). 4380 records from SMNS Palaeontological collection - Fossil plants. 2 records from Geneva Herbarium – Boissier's Flora Orientalis (G-BOIS). 27 records from Cnidaria MZS. 4904 records from Bacteria Collection in BCRC. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 1319 records from Collection Paleoanthropology SMF. 1 records from The velvet spiders: an atlas of the Eresidae (Arachnida, Araneae). 610 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 19929 records from Global compendium of Aedes aegypti occurrence. 1440 records from Museum TwentseWelle (NL) - Fossil Ammonites Collection. 8238 records from Wilson Botanical Garden - Las Cruces Biological Station. 2387 records from The French Collection of Medicago truncatula. 4085 records from SMNS Palaeontological collection - Tertiary mammals. 1028 records from SDSM Invertebrate Collections. 7 records from Herbarium - Las Cruces Biological Station. 11 records from Speothos Venaticus por Guillermo Gil. 3500 records from Naturalis National Natural History Museum (NL) – Cnidaria and Porifera fossils. 3250 records from SMNS Palaeontological collection - Invertebrates (Palaeozoic, Mesozoic). 44400 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 207205 records from SysTax - Botanical Gardens. 3852 records from BioFresh Pond Data. 145439 records from Palaeobiology - Vertebrate Fossils Collection - Mammalia - Royal Ontario Museum. 50682 records from CZE National PGR Inventory. 5 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 500808 records from Neptune Deep-Sea Microfossil Occurrence Database. 6529 records from Palaeontologische Sammlung der Freien Universitaet Berlin. 724 records from Guadeloupe_Ananas. 2 records from E. C. Smith Herbarium (ACAD). 30 records from Collection scientifique et pédagogique de l'Ecole Normale Supérieure de Lyon. 1761 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 433 records from Geneva Herbarium – General Collection (G). 2219 records from BoGART. 25006 records from Collection Paleontology - GPIT. 73 records from Fossil (JNHM-FO). 433 records from Guadeloupe_Ignames. 7216 records from AMNH Invertebrate Paleontology Collection. 458 records from Barley French National Collection. 29878 records from International Fossil Shell Museum (NL) - Mollusca Collection. 2485 records from Museum TwentseWelle (NL) - Fossil Sponges Collection. 5 records from National Museum of Natural Science. 51 records from Colección de Aráceas del Jardín Botánico San Jorge.
Keywords: GBIF; biodiversity; species occurrences